(untitled) (Nordic Journal of African Studies, 2018)
This article investigates how recently-constructed sites that anchor memories of anti-colonial resistance and national liberation have changed the urban landscape of the Namibian capital, Windhoek. The discussion is focused on the Namibian Independence Memorial Museum and the Genocide Memorial. These North-Korean-built monuments in a prominent hilltop position central Windhoek have significantly altered the city’s skyline with their massive aesthetics of Stalinist realism. Built in a particular position, they have replaced an infamous colonial memorial, the ‘Windhoek Rider’, and dwarf the ‘Alte Feste’ fort and the ‘Christuskirche’, iconic German colonial remnants of the built environment.